Validity and Reability Test of Indonesian Version of World HealthOrganization Quality of Life-HIV BREF Questionnaire to MeasureThe Quality of Life Patients with HIV/AIDS - Muhammad, Nanda N.; Shatri, Hamzah; Djoerban, Zubairi (UI Scholars Hub, 2017)
Introduction. Health-related quality of life among HIV patients can be used as one of several indicators of successful therapy. WHOQOL-HIV BREF questionnaire is one of the instruments used to assess the patients’ quality of life that has been used in many countries, but never been tested for its validity and reliability in Indonesia. This study aims to determine the validity and reliability of the questionnaire WHOQOL-HIV BREF in bahasa Indonesia as a tool for measuring the quality of life of HIV patients. Methods. A cross-sectional study was conducted in HIV Integrated Service Unit Cipto Mangunkusumo General Hospital (RSCM) Jakarta in November 2016 with consecutive sampling method. The study was conducted in two phases: first phase for the language and cultural adaptation process and second phase to test the validity and reliability of the questionnaire. Results. Fifty six respondents filled the questionnaire, 69.6% of them were male. Using a multi-trait scaling analysis, correlation coefficient value had a high correlation with the total score domain. This meant that it had a good validation. Correlation between questionnaire domain WHOQOL-HIV BREF and SF-36 questionnaire domain obtained 6 significant domains that shown strong correlation coefficient (r = 0.60 to 0.79; p <0.005). Reliability of the questionnaire was assessed by intraclass correlation coefficient of each domain, which was range from 0.401 to 0.484 with Cronbach Alpha 0.513 to 0.798 . Conclusions. The questionnaire WHOQOL-HIV BREF in the Indonesian language is valid and reliable.